2001
DOI: 10.1016/s0002-9394(01)01227-2
|View full text |Cite
|
Sign up to set email alerts
|

Visual field loss associated with vigabatrin: pathological correlations

Abstract: Pathological changes are reported in the anterior visual pathways of a 41 year old man with complex partial seizures treated with vigabatrin who developed bilateral visual field constriction. There was peripheral retinal atrophy with loss of ganglion cells and loss of nerve fibres in the optic nerves, chiasm, and tracts. No evidence of intramyelinic oedema was seen. These findings suggest that the primary site of injury lies within the ganglion cells in the retina. The degree of atrophy seen would suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 12 publications
4
18
0
Order By: Relevance
“…The reversible change in the electrooculogram response was also in agreement with a dysfunction of the functional relationship between photoreceptors and the retinal pigment epithelium (Arndt et al, 1999; Comaish et al, 2002; van der Torren et al, 2002). As in VGB-treated animals (Butler et al, 1987; Duboc et al, 2004; Wang et al, 2008), an histological examination of the retina from a VGB-treated patient confirmed major photoreceptor degeneration (Ravindran et al, 2001). However, in this more recent study, the primary site of injury was located within RGCs (Ravindran et al, 2001).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The reversible change in the electrooculogram response was also in agreement with a dysfunction of the functional relationship between photoreceptors and the retinal pigment epithelium (Arndt et al, 1999; Comaish et al, 2002; van der Torren et al, 2002). As in VGB-treated animals (Butler et al, 1987; Duboc et al, 2004; Wang et al, 2008), an histological examination of the retina from a VGB-treated patient confirmed major photoreceptor degeneration (Ravindran et al, 2001). However, in this more recent study, the primary site of injury was located within RGCs (Ravindran et al, 2001).…”
Section: Discussionmentioning
confidence: 67%
“…As in VGB-treated animals (Butler et al, 1987; Duboc et al, 2004; Wang et al, 2008), an histological examination of the retina from a VGB-treated patient confirmed major photoreceptor degeneration (Ravindran et al, 2001). However, in this more recent study, the primary site of injury was located within RGCs (Ravindran et al, 2001). This location was subsequently confirmed in more patients using in vivo imaging techniques of the retina, in both VGB-treated infants (Buncic et al, 2004; Frisen and Malmgren, 2003) and VGB-treated adult patients (Viestenz et al, 2003; Wild et al, 2006).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…1 We also have demonstrated widespread abnormalities in retinal electrophysiological function in patients treated with vigabatrin. 19 Cone system function, particularly those responses dependent on inner retinal function-flicker and oscillatory responses-was most affected by vigabatrin. Abnormalities in flicker and oscillatory ERG responses depend on function of GABA rich cells in inner retina and correlated strongly with visual field deficits.…”
Section: Discussionmentioning
confidence: 95%
“…4 Despite this retinal toxicity, the drug remains a third-line treatment for refractory complex partial seizures in adults and the first-line treatment in infantile spasms. 35 Damage in RGCs was confirmed by in vivo imaging techniques in both infants and adults. They described a disorganization of the photoreceptor nuclear layer, with displaced photoreceptor nuclei moving towards the RPE and sclera.…”
Section: Taurine Depletion Induced By Pharmacologic Agentsmentioning
confidence: 84%